Development of the world oil market and prerequisites for its transformation - A. Sh. Suleimenova; A. Zh. Panzabekova (Экономика: стратегия и практика)
Recently, the world oil market has been experiencing significant difficulties, which have led to global economic imbalances. These imbalances are closely related to market changes, when oil prices fall sharply, and world oil supply far exceeds world demand. However, this was not always the case. Back in the early 2000s, researchers predicted the achievement of a “peak in oil demand”, arguing that world oil production would soon reach its peak. Moreover, the constant rise in oil prices has led to the constant search for new fields and the transfer of wealth from importing countries to oil exporting countries. Such events formed a new stage in the development of the world oil market.In general, in the entire history of the development of commercial oil, the world oil market has undergone many changes, which determined its stages of development. This was the main purpose of this article - a phased analysis of the development of the world oil market, as well as a study of its characteristics, features and the transformational phenomena that have arisen. The constant geopolitical clashes between exporting countries and oil importing countries lead to significant diversification of the institutional structure of the oil market and the flexibility of functioning mechanisms. And technological progress, which entailed structural changes in energy consumption, is transforming the world towards the use of low-carbon energy sources and a worldwide reduction in oil consumption.